2019
DOI: 10.1080/20002297.2019.1663084
|View full text |Cite
|
Sign up to set email alerts
|

Composition and maternal origin of the neonatal oral cavity microbiota

Abstract: Background: The origin of the initial oral microbiota in neonates still remains poorly understood. Objective: The aim of this study was to understand how the maternal microbiota contributes to the initial neonatal oral microbiota. Design: Twelve mother-neonate pairs with samples from the maternal oral mucosa, uterine cervix and placenta and the neonatal oral cavity immediately after birth were studied. The microbiota composition and diversity were characterized by 16S rRNA gene sequencing (V3-V4 region). The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 36 publications
(52 reference statements)
1
24
0
1
Order By: Relevance
“…The first colonizing bacteria enter the intestine through the oral cavity. In spite of some authors proposing that the birth canal microbiota is the most decisive modulator on infants' oral and gut microbiota, recent studies suggest that the microbiota of the oral cavity in the neonate might have a prenatal origin, preceding the birth canal exposure [33]. Although an imbalance in the birth canal can affect the neonate's oral microbiota.…”
Section: Gut Colonizationmentioning
confidence: 99%
“…The first colonizing bacteria enter the intestine through the oral cavity. In spite of some authors proposing that the birth canal microbiota is the most decisive modulator on infants' oral and gut microbiota, recent studies suggest that the microbiota of the oral cavity in the neonate might have a prenatal origin, preceding the birth canal exposure [33]. Although an imbalance in the birth canal can affect the neonate's oral microbiota.…”
Section: Gut Colonizationmentioning
confidence: 99%
“…Between individuals the microbiota composition varies according to age, sex, and diet in health and disease, in addition to geographical variations [13, 14]. The human microbiota starts to develop gradually before and after the delivery [15-17]. Most of these initial changes in the bacterial microbiota composition start to settle after some months of life, also in the oral cavity [18-28].…”
Section: Introductionmentioning
confidence: 99%
“…This dogma has been challenged by several publications suggesting the presence of bacteria in the fetal environment including inside the placenta [1][2][3][4][5][6][7]. Studies using combinations of quantitative PCR (qPCR), fluorescence in situ hybridization (FISH) and next-generation sequencing techniques propose the existence of a "placental microbiome" [1,2,[8][9][10][11][12][13][14][15][16][17][18]. More generally, bacterial species were found in placenta, amniotic fluid, fetal gut, meconium and the neonate's mouth, suggesting a microbial colonization of the fetus [1,15,19].…”
Section: Introductionmentioning
confidence: 99%
“…Studies using combinations of quantitative PCR (qPCR), fluorescence in situ hybridization (FISH) and next-generation sequencing techniques propose the existence of a "placental microbiome" [1,2,[8][9][10][11][12][13][14][15][16][17][18]. More generally, bacterial species were found in placenta, amniotic fluid, fetal gut, meconium and the neonate's mouth, suggesting a microbial colonization of the fetus [1,15,19]. Interestingly, reports indicated that variations in the bacterial composition of the "placental microbiome" were associated with pregnancy outcomes such as preterm birth, chorioamnionitis, macrosomia, gestational diabetes mellitus, excess gestational weight gain, low birth weight, and pre-eclampsia [2,8,9,11,17,18,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%